Analysis of community economic empowerment from the perspective of Islamic economics: Case study of rice farmers of Siundol Padang Lawas - Nasution, Arifah; Arif, Muhammad; Daulay, Aqwa Naser (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2024)
This research analyzes community economic empowerment from an Islamic economic perspective, focusing on the case study of Siundol rice field farmers in Padang Lawas. Utilizing a qualitative method with a case study approach, data was collected through interviews, observations, and documentation. The findings indicate that the economic empowerment of the Siundol rice farming community in Padang Lawas is not yet optimal, primarily due to several factors: limited access to capital, low levels of education and skills, minimal access to information and technology, weak farmer institutions, and insufficient government involvement in empowering the community's economy. From an Islamic economic perspective, community economic empowerment should adhere to the principles of Islamic sharia, which include justice, balance, togetherness, and sustainability. Public interest statements Several steps are recommended to enhance the economic empowerment of the Siundol rice farming community: increasing access to capital through sharia-compliant financing, providing education and training for farmers, improving access to information and technology, strengthening farmer institutions, and enhancing the government's role in community economic empowerment Article Info: Received 6/10/2024 | Revised: 9/27/2024 | Accepted: 9/23/2024 | Online First 9/27/2024